Disappearance of Antibodies to Factor VIII in a Patient with Acquired Haemophilia and Carcinoma of the Pancreas During Cytotoxic Therapy with Fluorouracil and CCNU - Rhodes, E G H; Boesen, E A M; Corringham, R E T; Matthews, K B; Tuddenham, E G D; Kernoff, P B A (Thrombosis and Haemostasis, 1984)
An inhibitor to clotting factor VIII (anti-VIII: C) developed in a 70 year old woman with carcinoma of the pancreas three months after palliative by-pass surgery. A life-threatening sublingual haemorrhage was controlled by infusion of human factor VIII concentrate in high dosage. With the objective of reducing pancreatic tumour size, combination cytotoxic therapy with fluorouracil and CCNU was given. Reduction in the size of the tumour was associated with disappearance of anti-VIII:C, reappearance of normal quantities of clotting factor VIII (VIII: C) in the plasma and resolution of the bleeding tendency. The anti-VIII: C was characterised as being predominantly of the IgG4 sub-class with k light chains. In vitro and in vivo studies showed the inactivation of VIII: C by anti-VIII: C was markedly non-linear. Normal quantities of factor VIII coagulant antigen (VIII: CAg) were detected in the patient’s plasma when VIII: C levels were negligible.
Keywords: Acquired haemophilia; Factor VIII antibodies; Carcinoma of pancreas; CCNU; Fluorouracil